THE STUDY OF LINGUISTIC ON MINAHASA ETHNIC VOCAL MUSIC - Sanger, Maikel B.G. (IJRDO- Journal of Educational Research, 2017)
Some research states that music is a language, both of which use sound media. The rhythm of language also allows the same rhythm of music for a particular culture language. The Minahasa ethnic group has a diverse array of cultural traditions such as language and culture. This ethnic has a series of language types with each accent or a distinctive intonation that is said to be unique. On the other hand, its distinctive singing tradition is also very united with the people who live in it. If a typical accent is part of the Minahasa language language and the distinctive singing tradition is part of the Minahasa culture, can both be linked? Is the Minahasa way of singing influenced by the accent of the language? By looking at these problems, the researcher wanted to give an idea of how the language relation by way of singing of Minahasa people through the title of Linguistic Review on Minahasa Vocal Music. To answer the problem, the researcher uses the C. Dalhaus method of formal analysis: explains the structure of a work in terms of function and relationship between sections and elements, energetic interpretation: relates to the phase of movement or stretch of the tension, gestalt analysis: view the work as overall, hermeneutics: the interpretation of music in the context of an emotional statement or an external meaning. The research titled Linguistic Review of Minahasa Ethnic Vocal Music is a multi-disciplinary research because it will discuss two different disciplines of language discipline and music science. This research is categorized as descriptive research because it will give description about how the elements of language process in the way of singing people Minahasa.